2014
DOI: 10.1186/s13041-014-0067-9
|View full text |Cite
|
Sign up to set email alerts
|

5-mehtyltetrahydrofolate rescues alcohol-induced neural crest cell migration abnormalities

Abstract: BackgroundAlcohol is detrimental to early development. Fetal alcohol spectrum disorders (FASD) due to maternal alcohol abuse results in a series of developmental abnormalities including cranial facial dysmorphology, ocular anomalies, congenital heart defects, microcephaly and intellectual disabilities. Previous studies have been shown that ethanol exposure causes neural crest (NC) apoptosis and perturbation of neural crest migration. However, the underlying mechanism remains elusive. In this report we investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…Folate or folic acid is already present in prenatal supplements and as a food supplement in North America for protection against congenital neural tube defects, including those associated with alcohol exposure (Bailey et al., ; Serrano et al., ; Shi et al., ). However, current recommended supplement levels may not be sufficient to prevent alcohol‐induced congenital heart defects (CHDs) (Huhta and Linask, ).…”
mentioning
confidence: 99%
“…Folate or folic acid is already present in prenatal supplements and as a food supplement in North America for protection against congenital neural tube defects, including those associated with alcohol exposure (Bailey et al., ; Serrano et al., ; Shi et al., ). However, current recommended supplement levels may not be sufficient to prevent alcohol‐induced congenital heart defects (CHDs) (Huhta and Linask, ).…”
mentioning
confidence: 99%
“…Ethanol is a well-known teratogen causing craniofacial malformations (Schardein and Macina 2006) and its toxic effects on NCCs have often been investigated. It was previously shown that ethanol caused apoptotic cell death (Yan et al 2010) and inhibited migration (Shi et al 2014) of NCCs. In the present study, both reduced cell number and inhibited migration of cNCCs were observed as the effects of ethanol, although the effective concentration of ethanol was relatively higher than those reported in previous studies, probably because of species and strain differences in the susceptibility to ethanol (Wentzel and Eriksson 2008).…”
Section: Discussionmentioning
confidence: 99%
“…) and inhibited migration (Shi et al. ) of NCCs. In the present study, both reduced cell number and inhibited migration of cNCCs were observed as the effects of ethanol, although the effective concentration of ethanol was relatively higher than those reported in previous studies, probably because of species and strain differences in the susceptibility to ethanol (Wentzel and Eriksson ).…”
Section: Discussionmentioning
confidence: 99%
“…While 1% ethanol exposure did not affect NPB ( msx1 , pax3 and zic1 ) and NC ( snai2 ) specifier genes, it more specifically impaired the expression of genes involved in NCCs migration at a later stage, which has been proposed to be the cause of reduced craniofacial cartilages [41]. Because alcohol consumption reduces folic acid uptake, the same group examined a possible link between the two pathways.…”
Section: Craniofacial Disorders Modeled In Xenopusmentioning
confidence: 99%
“…Because alcohol consumption reduces folic acid uptake, the same group examined a possible link between the two pathways. Microinjection of 5-mehtyltetrahydrofolate (5-MTHF), the most bioactive form of folic acid, prior to ethanol exposure was able to partially rescue the expression of genes associated with NCCs migration in these embryos [41], suggesting that 5-MTHF could be beneficial for treating FAS. However, the authors did not directly evaluate whether the treatment could also rescue craniofacial structures in these tadpoles.…”
Section: Craniofacial Disorders Modeled In Xenopusmentioning
confidence: 99%